Detection of Adulteration and Pesticide Residues in Chinese Patent Medicine Qipi Pill Using KASP Technology and GC-MS/MS - Wang, Gang; Bai, Xuanjiao; Chen, Xiaochen; Ren, Ying; Pang, Xiaohui; Han, Jianping (Frontiers in Nutrition, 2022)
Abstract Chinese patent medicines (CPMs) are of great value for the prevention and treatment of diseases. However, adulterants and pesticide residues in CPMs have become the ‘bottleneck’ impeding the globalization of traditional Chinese medicine. In this study, 12 batches of commercially available Qipi pill (a famous CPM recorded in Chinese Pharmacopoeia) from different manufacturers were investigated to evaluate their authenticity and quality safety. Considering the severely degraded DNA in CPMs, kompetitive allele specific PCR (KASP) technology combined with DNA mini-barcodes was proposed for the quality regulation of a large number of products in CPM market. The residues of four kinds of pesticides including pentachloronitrobenzene (PCNB), hexachlorocyclohexane (HCH), aldrin and dichlorodiphenyltrichloroethane (DDT) were quantified using gas chromatography and tandem mass spectrometry (GC-MS/MS). The results indicated that in two of the 12 batches of Qipi pill, the main herbal ingredient Panax ginseng was completely substituted by P. quinquefolius, and one sample was partially adulterated with P. quinquefolius. The PCNB residue was detected in 11 batches of Qipi pill, ranging from 0.11 mg/kg to 0.46 mg/kg, and the prohibited pesticide HCH was present in four samples. Both adulteration and banned pesticides were found in two CPMs. This study suggests that KASP technology combined with DNA mini-barcodes can be used for the quality supervision of large sample size CPMs with higher efficiency but lower cost. Our findings also provide the insight that pesticide residues in CPMs should be paid more attention in the future.